Nonleukemic granulocytic sarcoma of kidney with mixed phenotype blasts: A diagnostic dilemma - Vinita Agrawal; Ajay Gupta; Ritu Gupta; Mehar Chand Sharma; Prasenjit Das (Wolters Kluwer Medknow Publications, 2011)
Granulocytic sarcoma (GS) usually presents concomitantly with or after the onset of acute myeloid leukemia, blastic phase of chronic myeloid leukemia (CML), or myelodysplastic syndromes. Rarely, it may present even before the onset of overt leukemia and when so, it is often misdiagnosed. We are reporting a case of GS of kidney presenting as an isolated renal mass with normal laboratory investigations including a normal peripheral blood smear. It was initially misdiagnosed as lymphoma as the blasts, in addition to the morphological similarity with lymphoma cells, also showed positive immunohistochemistry for B cell markers. Based on further investigations including immunophenotyping and cytogenetic studies, a final diagnosis of CML-blast crisis (mixed phenotype) presenting initially as GS was made. To the best of our knowledge, this is the first antemortem report of nonleukemic GS presenting as kidney mass that later on progressed to CML-blast crisis with mixed phenotype blasts.